Pharmacokinetics of ceftiofur sodium in equine pregnancy. Issue 6 (19th March 2017) - Macpherson, M. L.; Giguère, S.; Pozor, M. A.; Runcan, E.; Vickroy, T. W.; Benson, S. A.; Troedsson, M. H. T.; Hatzel, J. N.; Larson, J.; vanden Berg, E.; Kelleman, A. A.; Sanchez, L. C.; et al.
Abstract : Eleven pregnant pony mares (D270‐326) were administered ceftiofur sodium intramuscularly at 2.2 mg/kg ( n  = 6) or 4.4 mg/kg ( n  = 5), once daily. Plasma was obtained prior to ceftiofur administration and at 0.5, 1, 2, 4, 8, 12, and 24 hr after administration. Eight pony mares were re‐enrolled in the study at least 3 days from expected foaling to ensure steady‐state concentrations of drug at the time of foaling. Mares were administered ceftiofur sodium (4.4 mg/kg, IM) daily until foaling. Parturition was induced using oxytocin 1 hr after ceftiofur sodium administration. Allantoic and amniotic fluid, plasma, and colostrum samples were collected at time of foaling. Serial foal plasma samples were obtained. Placental tissues were collected. Desfuroylceftiofur acetamide (DCA) concentrations were measured in samples by high‐performance liquid chromatography (HPLC). Mean (± SD ) peak serum concentrations of DCA were 3.97 ± 0.50 μg/ml (low dose) and 7.45 ± 1.05 μg/ml (high dose). Terminal half‐life was significantly ( p  = .014) shorter after administration of the low dose (2.91 ± 0.59 hr) than after administration of the high dose (4.10 ± 0.72 hr). The mean serum concentration of DCA from mares at time of foaling was 7.96 ± 1.39 μg/ml. The mean DCA concentration in colostrum was 1.39 ± 0.70 μg/ml. DCA concentrations in allantoic fluid, amniotic fluid, placental tissues, and foal plasma were below the limit of quantification (<0.1 μg/ml) and below the minimum inhibitory concentration of ceftiofur against relevant pathogens. These results infer incomplete passage of DCA across fetal membranes after administration of ceftiofur sodium to normal pony mares.